1992
DOI: 10.1002/1097-0142(19921015)70:8<2087::aid-cncr2820700813>3.0.co;2-p
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for an association between hairy cell leukemia and renal cell and colorectal carcinoma

Abstract: Background. Hairy cell leukemia (HCL) has been associated with several disease states. In this study, a possible association is reported between HCL and renal cell carcinoma (RCC) and colorectal carcinoma (CRC). Methods. A retrospective study of the case records of 50 patients with HCL in a study of α‐interferon (α‐IFN) treatment of HCL. Results. Three of 50 patients with HCL studied had RCC, and 2 of these also had CRC. In addition, two other patients had CRC. The other malignant lesions developed either befo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
2

Year Published

1995
1995
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 22 publications
0
12
0
2
Order By: Relevance
“…Few epidemiological studies from population‐based cancer registries are reported. Second malignancies have been reported in the literature in 4–24% of patients with HCL (Table ), in epidemiologic studies (Bernstein et al , ; Kurzrock et al , ; Federico et al , ; Paltiel et al , ; Hisada et al , ), prospective studies (clinical trials) (Kampmeier et al , ; Pawson et al , ; Cheson et al , ; Flinn et al , ) and retrospective studies (single‐institute series) (Jacobs et al , ; Nielsen et al , ; Troussard et al , ; Au et al , ; Saven et al , ; Goodman et al , ; Maloisel et al , ). The rate of second malignancies reported in this current study (10%) is in line with these previous reports, including those from population‐based cancer registries.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Few epidemiological studies from population‐based cancer registries are reported. Second malignancies have been reported in the literature in 4–24% of patients with HCL (Table ), in epidemiologic studies (Bernstein et al , ; Kurzrock et al , ; Federico et al , ; Paltiel et al , ; Hisada et al , ), prospective studies (clinical trials) (Kampmeier et al , ; Pawson et al , ; Cheson et al , ; Flinn et al , ) and retrospective studies (single‐institute series) (Jacobs et al , ; Nielsen et al , ; Troussard et al , ; Au et al , ; Saven et al , ; Goodman et al , ; Maloisel et al , ). The rate of second malignancies reported in this current study (10%) is in line with these previous reports, including those from population‐based cancer registries.…”
Section: Discussionmentioning
confidence: 99%
“…In this study there was no significant difference in the incidence of additional malignancies between the different first‐line treatments. However, data in the literature is controversial, with some studies suggesting interferon treatment increases the risk of developing second malignancies (Nielsen et al , ; Kampmeier et al , ; Kurzrock et al , ) whereas other studies suggest that it is not a risk factor. Pentostatin does not appear to increase the risk of second malignancies (Kurzrock et al , ; Au et al , ; Cheson et al , ; Flinn et al , ; Maloisel et al , ), whereas data with cladribine are conflicting, with some studies reporting an increased risk (Saven et al , ; Cheson et al , ; Goodman et al , ), although others have not found an association (Kurzrock et al , ; Au et al , ).…”
Section: Discussionmentioning
confidence: 99%
“…Some studies showed that patients with HCL have an increased risk of second malignancy, either in a form of synchronous disease [7-10] or in a form of an increased incidence of a second neoplasm after the treatment of HCL [11-13]. Among malignancies with synchronous occurrence, the most frequent is the occurrence with other haematopoietic malignancies [14-21], B-cell lymphomas in the first place, and very rarely also with T-cell neoplasms.…”
Section: Discussionmentioning
confidence: 99%
“…In a report involving 350 HCL patients there appeared to be no significant excess of solid tumors compared to the expected incidence; however, an increased number of cases of myeloma and lymphoma were documented (107,(115)(116)(117). In some series, however, it has been suggested that renal carcinoma, colon carcinoma and skin cancers may show a borderline increase in incidence (118,119). When comparing this study to others, it appears that the only true increase relates to lymphoma and myeloma.…”
Section: Cytogenetics and Geneticsmentioning
confidence: 96%